(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Clinical pathway is a management tool utilized in hospitals in order to reduce variation in medical care as well as control health quality. Poor adherence to the clinical pathway documents most probably leads to deficiency in quality of care. This paper presents the result of an investigation for the role of clinical pathway document component (design) on the use of the clinical pathway tool in practice. We checked the content of three clinical pathway designs using the Integrated Care Pathway Appraisal Tool (ICPAT). Negative correlation between the compliance to ICPAT indicators and the completeness of third clinical pathway design has been obtained. Standard criteria in designing clinical pathway shows discrepancy which might be due to reluctances among the users to follow the lengthy procedure. In conclusion, userâ€™s preferences need to be considered for more practical use of clinical pathway beside the standard documentation perfection in order to achieve its objectives.Â